The impact of chemical composition of oxygenated fuels on morphology and nanostructure of soot particles. (1st January 2020) - Verma, Puneet; Jafari, Mohammad; Rahman, S.M. Ashrafur; Pickering, Edmund; Stevanovic, Svetlana; Dowell, Ashley; Brown, Richard; Ristovski, Zoran
Abstract: Over the years, oxygenated fuels such as biodiesel and alcohol fuels have been useful in reducing particulate matter (PM) emissions of diesel engines. The presence of oxygen in the fuel impacts the soot oxidation process and thus the morphology and nanostructural characteristics of soot particles change. The nanostructure characteristics of soot particles hold an importance for their oxidation reactivity and toxicity. Higher reactivity and exposure of soot particles to oxygen will affect the regeneration and filtration efficiency of diesel particulate filters. In this study, we investigate the impact of oxygen functional groups on morphology and nanostructure of soot particles by blending different types of essential oil in diesel. The test fuels were prepared by mixing orange oil, tea tree oil, eucalyptus oil and coconut biodiesel to keep an overall oxygen content of 0 and 2.2%. Transmission electron microscopy was used to investigate the physical changes in the nanostructure of soot particles. The primary particle diameter decreases, and fractal dimension of soot aggregates increases for oxygenated fuels. Microscopy reveals that the arrangement of carbon lamellae within the soot particles changes significantly with use of oxygenated as observed by the changes in fringe length, fringe tortuosity and fringe separation distance. Lower fringe length, higher fringe tortuosity and fringe separation distance shows disordered arrangement of carbon layers with more possibility of oxygen attack. The different structural characteristics for oils having same oxygen content shows that formation and structure of soot particles strongly depend upon chemical structure and composition of the fuel.